Gradual Application of Potassium Fertilizer Elevated the Sugar Conversion Mechanism and Yield of Waxy and Sweet Fresh-Eaten Maize in the Semiarid Cold Region - Li Yang; Yu Xin Chi; Yu Feng Wang; Muhammad Zeeshan; Xun Bo Zhou (Journal of Food Quality)
Fresh-eaten maize (Zea mays L.) is favored by consumers for its unique flavor, good health, and medical effects. Heilongjiang province is a semiarid cold region with the annual output of 3.35 billion ears, and the demand for fresh eaten maize is increasing in the region. Therefore, improving its yield and quality is urgently needed in this area. In this study, two of thirty varieties (waxy maize Jin-262 and sweet maize Jingke-183) were used and five proportions of potassium (K2O, 120 kg/ha) were applied at sowing, jointing, and large trumpet stages to identify the high yield and quality of fresh-eaten maize under a semiarid cold ecological condition in Daqing, Heilongjiang province, China, during 2017-2018. The results from the screening of eighteen maize varieties showed that waxy maize Jin-262 and sweet maize Jingke-183 had higher starch content and soluble sucrose contents than those of other varieties. While the potassium proportions application during the sowing (20%), jointing (40%), and large trumpet stages (40%) had further significantly increased the starch content, soluble sugar content, sucrose content, and sucrose metabolic enzymes activities of Jin-262 and Jingke-183, however, the yields of Jin-262 and Jingke-183 had increased by applying potassium fertilizer during the sowing stages (50%) and jointing stages (50%). Considering the overall higher maize quality, we recommended the waxy maize Jin-262 and sweet maize Jingke-183 varieties along with application of 20% (sowing), 40% (jointing), and 40% (large trumpet stages) of 120 kg/ha potassium fertilizer for the improvement of grain quality of maize planting in the semiarid cold region. Otherwise, reasonable gradual potassium fertilization might be a wiser option.